PENGARUH MODAL INTELEKTUAL DAN PENGUNGKAPAN MODAL INTELEKTUAL PADA NILAI PERUSAHAAN YANG MELAKUKAN INITIAL PUBLIC OFFERING - Widarjo, Wahyu (UI Scholars Hub, 2011)
The objective of this research is to investigate the influence of intellectual capital performance and intellectual capital disclosure on the value of the firm after an initial public offering (IPO). The Value Added Intellectual Coefficient (VAICTM) method is used to measure of intellectual capital. Intellectual capital disclosure in this research is measure with Zingh and Zahn (2008) index, and value firm is determined by market value of the firm. The result of the analysis fails to support the first hypothesis that intellectual capital is affected to firm’s values. The result probably is an indication that market is incapable to assess the value of a company’s intellectual capital because it has no standardized measure and the limited quantitative disclosure regarding intellectual capital. The result of the study support the second hypothesis that intellectual capital disclosure influences positively to firm’s value. This matter is indication that intellectual capital disclosure will lessen asymmetry information so that assist the investor in valuations of performance company and can conduct the correct analysis regarding the company prospect in the future.